If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + -2) + 7 = 1 + -3w Reorder the terms: 3(-2 + w) + 7 = 1 + -3w (-2 * 3 + w * 3) + 7 = 1 + -3w (-6 + 3w) + 7 = 1 + -3w Reorder the terms: -6 + 7 + 3w = 1 + -3w Combine like terms: -6 + 7 = 1 1 + 3w = 1 + -3w Add '-1' to each side of the equation. 1 + -1 + 3w = 1 + -1 + -3w Combine like terms: 1 + -1 = 0 0 + 3w = 1 + -1 + -3w 3w = 1 + -1 + -3w Combine like terms: 1 + -1 = 0 3w = 0 + -3w 3w = -3w Solving 3w = -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. 3w + 3w = -3w + 3w Combine like terms: 3w + 3w = 6w 6w = -3w + 3w Combine like terms: -3w + 3w = 0 6w = 0 Divide each side by '6'. w = 0 Simplifying w = 0
| 4+v=3v-8 | | X=2(0) | | (-5)-(-2)=g+4 | | -60=6x-5y | | 34:4= | | -3(12-6x)=7(8-2x) | | (-35)=c+(-18) | | 5x+13=3x-93 | | X=2-2 | | $45.00-30%= | | -3(m-7)=2m-4 | | 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x |